Solution of the problems on the pipelined operator tree using characteristical matix - Thập, Lê Huy (Journal of Computer Science and Cybernetics, 2012)
The paper describes a representation of POT by n<span lang="SV" style="font-family: Symbol; font-size: 12pt; mso-ansi-language: SV; mso-bidi-font-family: "Times New Roman"; mso-fareast-font-family: "Times New Roman"; mso-fareast-language: VI; mso-bidi-language: AR-SA; mso-ascii-font-family: "Times New Roman"; mso-hansi-font-family: "Times New Roman"; mso-char-type: symbol; mso-symbol-font-family: Symbol;">´n characteristical square matrix and therefore, every operations on the POT such as cutting of the child vertices from the father’s vertex, collapsing of child vertices to the father’s vertex, local cuttings, finding the optimal query schedule and the cost balance,…, on the POT that are performed easier using the algorithms and processing of array and model programming language.